Ethnomathematics Exploration of Museum Gedung Arca (State Museum of North Sumatra) - Safriyanti, Safriyanti; Yahfizham, Yahfizham (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
Education and culture are two things that cannot be separated. In education there are cultural values ​​in it. Ethnomatematics is a blend of mathematics and culture. Ethnomatematics can improve students' mathematical abilities. By exploring the ethnomathematics of the Arca Building Museum or the State Museum of North Sumatra, students can get to know the culture and geometric concepts of flat shapes found in building forms and museum collections. The geometry of a flat shape is a form of geometry that has an area and a width. The aim of the research is to improve students' mathematics learning and mathematical abilities through geometric exploration of flat shapes in building shapes, collections, and collection placement in museums. The method I used in my research was qualitative research. The results of the research obtained are finding the geometric concept of flat shapes through the shape of the building, the collection, and the placement of the Museum collection. Ethnomatematics exploration is an alternative to improve mathematics learning and students' mathematical abilities. By exploring the concept of geometric shapes in the form of museum buildings, students can easily understand the mathematics of geometric shapes. Keywords: Ethnomathematics, Sculpture Building Museum, Flat Shape Geometry